Tantangan Guru PPKn dalam Meningkatkan Moralitas Siswa di SMP Ali Imron Medan - Fajar Tri Kesuma; Putri Arpani; Aprianta Tarigan; Ira Safitri (Universitas Methodist Indonesia, 2024)
This research aims to explore the challenges faced by Pancasila and Citizenship Education (PPKn) teachers in improving student morale at Ali Imron Middle School in Medan as well as the role of parents in shaping children's morals. The research method used is qualitative with data collection techniques through observation, interviews and documentation. The research results show that PPKn teachers face challenges such as lack of appreciation from students, impaired focus due to students' naughty behavior, and lack of family attention towards children. Parents also have an important role in shaping children's morals by not defending children without careful consideration. The implication of this research is the need for cooperation between teachers, parents and the community in creating a positive and inclusive learning environment in order to improve student morality. The contribution of this research lies in further understanding the challenges faced by Civics teachers in certain contexts and the importance of the role of parents in the moral formation of children, which can be the basis for developing more effective moral education strategies in the future.